DESIGN OF FAST DISSOLVING TABLET OF ATENOLOL USING NOVEL CO-PROCESSED SUPERDISINTEGRANT - Kumare, Mangesh M; Marathe, Rajendra P; Kawade, Rajendra M; Ghante, Mahavir H; Shendarkar, Giridhar R (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Atenolol is a recognized drug for hypertension therefore development of an FDT of Atenolol and to evaluate the effect of co-processed superdisintegrants on its disintegration time and release profile was the prime objective of this research work. Tablets were prepared by direct compression technique using two different superdisintegrants in combination by co-process mixing and by physical mixing. Croscarmellose sodium and Crospovidone were used as superdisintegrants in combinations in the different ratio (1:1, 1:2 & 1:3). The developed superdisintegrants were evaluated for angle of repose, Carr's index and Hausner's ratio in comparison with physical mixture of superdisintegrants. The angle of repose of the developed excipients was found to be < 250, Carr's index in the range of 10-15% and Hausner's ratio in the range of 1.11-1.14. Fast dissolving tablets of Atenolol were prepared using the co-processed superdisintegrants and evaluated for pre-compression and post compression parameters. Based on in-vitro dispersion time (approximately 20sec) CP1 formulation was tested for in-vitro drug release pattern in pH 6.8 Phosphate buffer and drug excipients interaction were studied with DSC. Among the designed formulations, the formulation (CP1) containing 4% w/w of co-processed superdisintegrants (1:1 mixture of Crospovidone and Croscarmellose sodium) emerged as the overall best formulation based on drug release characteristics in pH 6.8 phosphate buffer. Keywords: Atenolol, Crospovidone, Croscarmellose sodium, Co-processed Superdisintegrants, Fast dissolving tablet